Economic efficiency of rubber smallholders in Negeri Sembilan, Malaysia - Abdulrahman, Aliyu (2017)
Malaysia is one of the leading producers of natural rubber in the world. About 8.3 % of the total world’s rubber is produced in Malaysia. To be precise, Malaysia is currently the third biggest producer of natural rubber in the world and it’s the fifth largest consumer of rubber among the world’s largest exporters of rubber products (Malaysia Rubber Export Council, 2009). The industry employed more than 300, 000 workers and contributed RM 6.24 billion to the country's export earnings in 2015 (MPIC, 2017). Several studies were carried out on efficiency of rubber production in Malaysia, some studies were on either, allocative or technical efficiency or both (economic efficiency). The present study looked at the economic efficiency and was actually motivated by the fact that efficiency and productivity of Malaysian rubber production has been declining over the years as justified by the preliminary analysis done on nearly 30 year period from 1982-2012. The study therefore, examined not only the possibility of assessing the future survival and strength of rubber productivity in Peninsular Malaysia, but also in a disaggregated form since rubber is a perennial crop. In order to investigate the effects of perenniality on yield and productivity of rubber, both parametric and non-parametric techniques were applied. The determinants or factors militating against the rubber smallholders’ efficiency in Negeri Sembilan, Peninsular Malaysia, were also carried out.